2020
DOI: 10.1128/mbio.02540-20
|View full text |Cite
|
Sign up to set email alerts
|

The TLR3/IRF1/Type III IFN Axis Facilitates Antiviral Responses against Enterovirus Infections in the Intestine

Abstract: Enteroviruses infect gastrointestinal epithelium cells, cause multiple human diseases, and present public health risks worldwide. However, the mechanisms underlying host immune responses in intestinal mucosa against the early enterovirus infections remain elusive. Here, we showed that human enteroviruses including enterovirus 71 (EV71), coxsackievirus B3 (CVB3), and poliovirus 1 (PV1) predominantly induce type III interferons (IFN-λ1 and IFN-λ2/3), rather than type I interferons (IFN-α and IFN-β), in cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…Intracellular receptors such as MDA5 and RIG-I may be key in the detection of cytosolic dsRNA including poly(I:C) delivered via transfection. Other studies have suggested that IECs, including HT-29 and CaCo-2 cells can respond to longer poly(I:C) exposure than those used in the present study (6 h) [56]. Based on the aforementioned and our present observations it is possible to hypothesize that IECs are slightly more inert to exposure with PAMPs and less likely to respond to dsRNA (e.g., poly (I:C)) to avoid the continual induction of an inflammatory state in the gut.…”
Section: Discussionmentioning
confidence: 49%
“…Intracellular receptors such as MDA5 and RIG-I may be key in the detection of cytosolic dsRNA including poly(I:C) delivered via transfection. Other studies have suggested that IECs, including HT-29 and CaCo-2 cells can respond to longer poly(I:C) exposure than those used in the present study (6 h) [56]. Based on the aforementioned and our present observations it is possible to hypothesize that IECs are slightly more inert to exposure with PAMPs and less likely to respond to dsRNA (e.g., poly (I:C)) to avoid the continual induction of an inflammatory state in the gut.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, porcine epidemic diarrhea virus (PEDV) which also replicates in IECs, has been shown to inhibit IRF-1-dependent type III IFN production [ 52 ]. Furthermore, a recent report demonstrated a role for IRF-1 in the upregulation of type III IFNs in human IECs in response to enterovirus infection, confirming the relevance of this transcription factor in the cells that support RV replication [ 53 ].…”
Section: Discussionmentioning
confidence: 81%
“…This highlights a caveat of transcriptomic analysis, whereby the findings are influenced by the depth of sequencing required to pick up, in this case, these specific IFN genes. For example, mammalian reovirus infected T84 intestinal cells and enterovirus 71-infected HT29 cells express lower levels of IFNβ transcripts compared to IFNλ [21, 22]. As such the level of IFNα and/or IFNβ production in the HIEs could have been below the limit of detection of RNA-sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…While TLR1, 2 and 3 were detectable across all datasets, they were only differentially expressed in response to norovirus infection. TLR3 is primarily present in the endosomal compartment and senses double-stranded (ds) RNA [22, 23]. DsRNA is a RNA virus replication intermediate present during infection with all three viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation